BS EN 4056-005. Aerospace series. Cable ties for harnesses. Part 005. Plastic cable ties with metallic locking devices, operating temperatures -65 °C to 105 °C and -65 °C to 150 °C. Product standard (1st April 2021) - British Standards Institution,
No abstract available